The Development of Student Worksheets (LKPD) Based on Discovery Learning Procedure Text Material for Class VII SMP: Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Discovery Learning Materi Teks Prosedur Kelas VII SMP - Novita Sari; Ria Ariesta; Padi Utomo (UNIB Press, 2026)
This research aims to describe the needs analysis process, the design results, the results of development techniques, the results of the implementation of Discovery Learning-based LKPD procedural text material for class VII SMP students. This form of study is called Research and Development (R&D) using the ADDIE development model. Data collection techniques were carried out in the form of interviews and questionnaires. Interviews were carried out using interview guidelines to find out the situation in learning, and questionnaires were carried out to find out the results of validation tests and prasvcticality tests. The data analysis technique used is qualitative and quantitative analysis in the form of LKPD development process data, validation data by validators, and student assessment data to determine the practicality of LKPD. The research results were seen from the material expert validation process with a score percentage of 81.25% and design validation with a score percentage of 77.77%, thus reaching the feasible category. The results of the student assessment of the LKPD received a score of 4.35% in the very practical category. So it can be concluded that the Student Worksheet based on discovery learning, the procedural text material produced, is suitable and practical to use. Therefore, it can be concluded that the Discovery Learning-based procedure text LKPD for class VII junior high school is feasible and practical to use in learning.